Roles of social workers in bridging the gap between social policy and social action in youth unemployment in Nigeria - Fajimi , Babatunde Ayoola (American Journal of Social Sciences and Humanities, 2025)
Youth unemployment remains a persistent social issue in Nigeria, despite the implementation of social welfare policies and proactive measures by stakeholders in the social sector. Current interventions often do not match ongoing social actions hence the need for multisectoral approaches to address the problem. This study investigates the roles of social workers in bridging the gap between social policy and social action in order to mitigate youth unemployment in Nigeria. A correlational survey research design was utilised for this study. The study's population consisted of 6,047 registered social workers and the sample size of 360 participants was calculated using the Krejcie and Morgan table. The study employed a multi-stage sampling technique, incorporating disproportionate simple random sampling, purposive sampling, and snowball sampling, to select participants from the Social Work associations across Nigeria's six geopolitical zones. The validity of the research instrument was confirmed by expert scholars, and a test-retest reliability coefficient of 0.86 was obtained from a pilot study involving participants not included in the main sample. The questionnaire was administered electronically and responses analysed using both descriptive and inferential statistics. The study identified a relationship between social policy and social action but there is no synergy between policy formulation and social action. Consequently, the roles of social workers were not integrated into the interactions between social policy and social action. The government, Social Work professional associations, and other stakeholders should incentivise social workers to offer innovative interventions to unemployed youth in overcoming the challenges of unemployment and transitioning to entrepreneurship.